Novel Nanomaterials for Thermochemical Storage (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book offers recent developments in terms of thermochemical energy storage materials (TCM), covering the full temperature range of application, low, medium and high. Beginning with a review of the recent advancements in the field of adsorption thermal energy storage systems, this book goes on to discuss innovative TC nanomaterials, in terms of synthesis, characterization and validation.